Retinoid X receptor:vitamin D3 receptor heterodimers promote stable preinitiation complex formation and direct 1,25-dihydroxyvitamin D3-dependent cell-free transcription. - Lemon, B D (1997)
The numerous members of the steroid/nuclear hormone receptor superfamily act as direct transducers of circulating signals, such as steroids, thyroid hormone, and vitamin or lipid metabolites, and modulate the transcription of specific target genes, primarily as dimeric complexes. The receptors for 9-cis retinoic acid and 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], RXR and VDR, respectively, as members of this superfamily, form a heterodimeric complex and bind cooperatively to vitamin D responsive elements (VDREs) to activate or repress the transcription of a multitude of genes which regulate a variety of physiological functions. To directly investigate RXR- and VDR-mediated transactivation, we developed a cell-free transcription system for 1,25(OH)2D3 signaling by utilizing crude nuclear extracts and a G-free cassette-based assay. Transcriptional enhancement in vitro was dependent on purified, exogenous RXR and VDR and was responsive to physiological concentrations of 1,25(OH)2D3. We found that RXR and VDR transactivated selectively from VDRE-linked templates exclusively as a heterodimeric complex, since neither receptor alone enhanced transcription in vitro. By the addition of low concentrations of the anionic detergent Sarkosyl to limit cell-free transcription to a single round and the use of agarose gel mobility shift experiments to assay factor complex assembly, we observed that 1,25(OH)2D3 enhanced RXR:VDR-mediated stabilization or assembly of preinitiation complexes to effect transcriptional enhancement from VDRE-linked promoter-containing DNA.